Emotion regulation group therapy for deliberate self-harm: a multi-site evaluation in routine care using an uncontrolled open trial design. Issue 10 (5th October 2017) - Sahlin, Hanna; Bjureberg, Johan; Gratz, Kim L; Tull, Matthew T; Hedman, Erik; Bjärehed, Jonas; Jokinen, Jussi; Lundh, Lars-Gunnar; Ljótsson, Brjánn; Hellner, Clara
Abstract : Objective: Emotion regulation group therapy (ERGT) has shown promising results in several efficacy trials. However, it has not been evaluated outside a research setting. In order to increase the availability of empirically supported treatments for individuals with borderline personality disorder and deliberate self-harm, an evaluation of ERGT in routine clinical care was conducted with therapists of different professional backgrounds who had received brief intensive training in ERGT prior to trial onset. Design: Multi-site evaluation, using an uncontrolled open trial design with assessments at pretreatment, post-treatment and 6-month follow-up. Setting: 14 adult outpatient psychiatric clinics across Sweden. Participants: Ninety-five women (mean age=25.1 years) with borderline personality disorder (both threshold and subthreshold) and repeated self-harm were enrolled in the study. Ninety-three per cent of participants completed the post-treatment assessment and 88% completed the follow-up assessment. Primary and secondary outcome measures: Primary outcome was self-harm frequency as measured with the Deliberate Self-Harm Inventory. Secondary outcomes included self-harm versatility, emotion dysregulation, other self-destructive behaviours, depression, anxiety, stress symptoms and interpersonal and vocational difficulties. Intervention: ERGT is an adjunctive, 14-week, acceptance-based behavioural group treatment that directly targets both self-harm and its proposed underlying mechanism of emotion dysregulation. Results: At post-treatment, intent-to-treat analyses revealed a significant improvement associated with a moderate effect size on the primary outcome of self-harm frequency (51%, reduction; Cohen's d=0.52, p<0.001) as well as significant improvements in the secondary outcomes of self-harm versatility, emotion dysregulation, other self-destructive behaviours and general psychiatric symptomatology. These results were either maintained or further improved on at 6-month follow-up. Conclusions: ERGT appears to be a feasible, transportable and useful treatment for deliberate self-harm and other self-destructive behaviours, emotion dysregulation and psychiatric symptoms when delivered by clinicians in the community. Trial registration number: NCT01986257; results.